2018
DOI: 10.1021/acs.nanolett.7b05050
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Yu–Shiba–Rusinov States in Molecular Dimers on NbSe2

Abstract: Magnetic impurities have a dramatic effect on superconductivity by breaking the time-reversal symmetry and inducing so-called Yu–Shiba–Rusinov (YSR) low energy bound states within the superconducting gap. The spatial extent of YSR states is greatly enhanced in two-dimensional (2D) systems, which should facilitate the formation of coupled states. Here, we observe YSR states on single cobalt phthalocyanine (CoPC) molecules on a 2D superconductor NbSe2 using low-temperature scanning tunneling microscopy (STM) and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
137
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(146 citation statements)
references
References 44 publications
7
137
2
Order By: Relevance
“…Moreover, in the seminal experimental work on the competition between Cooper pairing and Kondo screening [21], it was further demonstrated that an increased exchange coupling between the magnetic impurity and the superconductor leads to a decrease of |ε B | and a crossing of ε B with the Fermi level accompanied by the inversion of the electron-hole spectral weight. Several other works followed presenting the requirement of topological Shiba bands for the observation of Majorana modes in atomic chains [22], the impact of magnetic anisotropy on YSR states [23], the influence of the dimensionality of the superconductor on the spatial coherence of the bound states [24], a detailed understanding of the orbital origin of YSR multiplets [25,26], the occurrence of YSR states in proximity-induced superconductor-molecule junctions [27], the spin polarization of YSR states [28], and coupling phenomena [29].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in the seminal experimental work on the competition between Cooper pairing and Kondo screening [21], it was further demonstrated that an increased exchange coupling between the magnetic impurity and the superconductor leads to a decrease of |ε B | and a crossing of ε B with the Fermi level accompanied by the inversion of the electron-hole spectral weight. Several other works followed presenting the requirement of topological Shiba bands for the observation of Majorana modes in atomic chains [22], the impact of magnetic anisotropy on YSR states [23], the influence of the dimensionality of the superconductor on the spatial coherence of the bound states [24], a detailed understanding of the orbital origin of YSR multiplets [25,26], the occurrence of YSR states in proximity-induced superconductor-molecule junctions [27], the spin polarization of YSR states [28], and coupling phenomena [29].…”
Section: Introductionmentioning
confidence: 99%
“…DOI: 10.1103/PhysRevLett.119.197002 Recent investigations of chains [1][2][3] and arrays [4,5] of magnetic atoms in contact with surfaces of s-wave superconductors in view of Majorana zero modes and topological superconductivity triggered renewed interest in the properties of the basic constituent of such systems, the individual magnetic adatom. Typically, such adatoms induce quasiparticle excitations inside the superconducting energy gap [6][7][8], referred to as Yu-Shiba-Rusinov (YSR) states, which hamper the identification of topologically nontrivial edge states [3,9], calling for a thorough characterization of all experimentally accessible properties of YSR states.Following the first experimental verification of YSR states of individual atoms using scanning tunneling spectroscopy (STS) [10], there were numerous experimental studies, focusing on orbital effects [11][12][13], magnetic anisotropy [14], effects of reduced dimensionality of the superconductor [15], effects of coupling [11,16], and the competition between Kondo screening and superconducting pairing [17,18]. However, the investigation of the spin polarization of the YSR state of individual atoms, which could serve as a fingerprint for the distinction from topological states [19], was so far restricted to theoretical predictions [6][7][8][20][21][22].…”
mentioning
confidence: 99%
“…Following the first experimental verification of YSR states of individual atoms using scanning tunneling spectroscopy (STS) [10], there were numerous experimental studies, focusing on orbital effects [11][12][13], magnetic anisotropy [14], effects of reduced dimensionality of the superconductor [15], effects of coupling [11,16], and the competition between Kondo screening and superconducting pairing [17,18]. However, the investigation of the spin polarization of the YSR state of individual atoms, which could serve as a fingerprint for the distinction from topological states [19], was so far restricted to theoretical predictions [6][7][8][20][21][22].…”
mentioning
confidence: 99%
“…In the case of graphene nanoribbons the behavior is more complex due to the existence of several YSR branches that give rise a to a continuum of in-gap excitations. [82][83][84][85][86] FIG. 9.…”
Section: Magnetic Ribbons Competing a Superconducting Proximity Effectmentioning
confidence: 99%